1987
DOI: 10.1097/00000658-198703000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy Post Peritoneovenous Shunt

Abstract: In 1942, 53% of medically treated patients with cirrhosis were dead 6 months after the onset of ascites. Only 30% survived 1 year. This dismal outlook has improved only slightly with advances in medicine. Yet, some internists reject the peritoneovenous shunt (PVS) for this fatal condition even if they are aware that a diminished blood volume causes the abnormal sodium retention responsible for ascites. Their objections are based on life-threatening complications of PVS, especially post shunt coagulopathy (PSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Moreover, although PV shunts may improve and stabilize renal function in some patients [66,67], they have so far not been shown to prolong survival significantly in patients with combined kidney and liver failure. In cirrhotic ascites in general, operative mortality rates up to 25 % have been reported, largely due to hepatic decompensation, disseminated intravascular coagulation, or septicemia [68,69]. In view of these risks, the unproven benefit, and a high incidence of shunt occlusion [70], PV shunting cannot generally be recommended for treatment of renal failure.…”
Section: Peritoneovenous Shuntsmentioning
confidence: 99%
“…Moreover, although PV shunts may improve and stabilize renal function in some patients [66,67], they have so far not been shown to prolong survival significantly in patients with combined kidney and liver failure. In cirrhotic ascites in general, operative mortality rates up to 25 % have been reported, largely due to hepatic decompensation, disseminated intravascular coagulation, or septicemia [68,69]. In view of these risks, the unproven benefit, and a high incidence of shunt occlusion [70], PV shunting cannot generally be recommended for treatment of renal failure.…”
Section: Peritoneovenous Shuntsmentioning
confidence: 99%
“…Several noncontrolled trials using TIPS in the management of variceal bleeding have been en~ouraging.~.~ However, there are few data concerning the usefulness of TIPS in the treatment of refractory as cite^.^ Apart from liver transplantation and obsolete procedures such as ascites ultrafiltration and reinfusion' and side-to-side portocaval shunt, the only available therapeutic approaches in this situation are large-volume paracentesis with albumin infusion and peritoneovenous These procedures are associated with significant complications or frequent hospital admissions and are unable to modify the poor prognosis of the patients. [8][9][10][11][12][13][14][15][16] A short-term study using TIPS in refractory ascites showed that the procedure allowed a better control of ascites and reversed renal sodium retention. 17 We report on the long-term clinical results of TIPS in patients with refractory ascites.…”
mentioning
confidence: 99%
“…In addition, patency of the vena cava, no history of cardiac pacemaker, no history of hepatic lobectomy, and no dilated intestine were included to secure a safe access route for transjugular transhepatic PVS. The exclusion criteria (i.e., cirrhosis and high risk for gastrointestinal bleeding) were added because of previous reports of severe adverse events resulting from PVS placement in cirrhotic patients [7,11,17,18]. Won and coworkers [7] reported that 63% of 55 patients with refractory ascites developed variceal bleeding after Denver shunt placement.…”
Section: Discussionmentioning
confidence: 99%